A Single-Subject Study of a Technology-Based Self-Monitoring Intervention - Vogelgesang, Kari L.; Bruhn, Allison L.; Coghill-Behrends, William L.; Kern, Amanda M.; Troughton, Leonard C. W. (Journal of behavioral education, 2016)
Students with ADHD often struggle with self-regulation skills. One strategy demonstrating considerable success in helping these students regulate their behavior is self-monitoring. Although there is an abundance of research on self-monitoring, research on the use of technology for self-monitoring is only beginning to emerge. The primary goal of this single-subject study was to examine the effects of an iPad application (SCORE IT) for self-monitoring on the behavior of three fifth-grade students with or at risk for ADHD who were exhibiting low rates of academic engagement in a general education environment. A secondary goal was to gain an in-depth understanding of the teacher's perceptions of the feasibility and value of the intervention. Overall, the SCORE IT intervention resulted in substantial improvements in academic engagement, and teacher perceptions of the feasibility and worth of the intervention were reported as highly favorable. Limitations and future directions for research are discussed.